Terrorism and the influence on the Comprehensive Security in Ecuador to 2023 (Revista de Ciencias de Seguridad y Defensa, 2023)
The present article analyzes the presence of supposed terrorism in Ecuador due to many terrorist actions in recent years that impact in the integral security, causing a generalized perception of insecurity in the population, as well as the problem of terrorism and its link with organized crime. Through mixed research methods, including surveys of future military leaders in the operational and strategic areas and interviews with high-level security experts, the perception of terrorism as a threat to integral security is explored. Possible connections between variables such as capacity, intention, motivation, and organized structure with terrorist acts in the country are also established. In addition, key patterns are identified, such as the preponderant role of drug trafficking in the financing of terrorist activities, the concentration of attacks in the Costa region, and the resurgence of incidents in 2022. The results suggest that, although criminal violence is a growing challenge, there is no compelling evidence suggesting the formal presence of terrorist groups in Ecuador. Rather, the challenge seems to come from criminal gangs linked to drug trafficking, whose motivations differ from those of terrorist organizations. These findings have important implications for Ecuadorian security policy, specifically in terms of designing comprehensive strategies that address the underlying factors behind the wave of criminal violence.
Keywords: terrorism; organized crime; violence; drug trafficking; comprehensive security